Student reading lists: evaluating the student experience at the University of Huddersfield. Issue 2 (3rd April 2017) - McGuinn, Kate; Stone, Graham; Sharman, Alison; Davison, Emily
Abstract : Purpose: The purpose of this paper is to evaluate the bespoke resource list management system (MyReading) at the University of Huddersfield. Design/methodology/approach: An online survey was designed to assess student use of MyReading and their views on potential improvements. The survey used closed questions designed to obtain quantitative data. Thematic analysis was used to analyse qualitative data obtained from open questions. Findings: The paper supports findings of another recent study which found that reading lists are perceived as more important by students than by lecturers. A variety of positive and negative themes emerged which pointed to this conclusion. Positive themes were: the perceived helpfulness of reading lists, students' view of MyReading as a starting point for independent further reading, ease of use of MyReading and the time saving afforded to students and the value students place on their reading lists as being "quality assured" by lecturers. Negative themes were: inconsistency in the length and structure of lists; concerns that some lists are not regularly updated; lack of awareness of functionality, revealing training needs for students and lecturers; and suggestions for future enhancements to MyReading. Another finding from the quantitative data is the clear link between low use of reading lists by students in certain schools and low use of other library resources. Practical implications: The research provides guidance to universities regarding future development of resource list management systems and promotional and training needs. Originality/value: The study adds rich information to the existing body of qualitative research on students' perceptions of their reading lists.